Can Older Workers Be Retrained? Canadian Evidence from Worker-Firm Linked Data - Tony Fang; Morley Gunderson; Byron Lee (Institute of Labor Economics (IZA), 2021)
Based on Statistics Canada's worker-firm matched Workplace and Employee Survey, our econometric analysis indicated that the average probability of receiving training was 9.3 percentage points higher for younger (25-49) compared to older (50+) workers. Slightly more than half of that gap is attributed to older workers having a lower propensity to receive training after controlling for the characteristics that affect training. Their lower propensity to receive training tended to prevail across 54 different training measures. We find that older workers can be trained, but this requires training that is designed for their needs including: slower and self-paced instruction; hands-on practical exercises; modular training components that build in stages; familiarizing them with new equipment; and minimizing required reading and the amount of material covered.
Keywords: J14; J18; J24; 330; training; older workers; worker-firm matched data; Canada